2011
DOI: 10.2460/javma.238.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and interobserver agreement for results of low-field magnetic resonance imaging in dogs with and without clinical signs of disk-associated wobbler syndrome

Abstract: Results suggested that variability exists among observers with regard to results of MRI in dogs with DAWS and that MRI could lead to false-positive and false-negative assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 29 publications
2
29
2
Order By: Relevance
“…The pathogenesis is complex and unclear. An example of this complexity is that Doberman Pinschers can have spinal cord compression but no clinical signs of cervical spondylomyelopathy …”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis is complex and unclear. An example of this complexity is that Doberman Pinschers can have spinal cord compression but no clinical signs of cervical spondylomyelopathy …”
Section: Introductionmentioning
confidence: 99%
“…Gait abnormalities are often one of the first noted signs in dogs with CSM and are observed as a slowly progressive hind limb ataxia or “wobbling” of the pelvic limbs . Additionally, thoracic limb abnormalities may manifest themselves as varying degrees of ataxia in combination with a short, stilted gait . Treatment options for CSM include conservative management or surgical decompression; however, the best option for treatment is still highly controversial .…”
mentioning
confidence: 99%
“…Although the authors of this study have already described the morphologic and morphometric cervical MRI findings of dogs with DA-CSM, clinically normal Doberman pinschers, and clinically normal English Foxhounds, no results have yet been reported on their intervertebral disk width [13-16]. These previous studies have demonstrated that the occurrence and degree of disk degeneration and protrusion could be considered part of normal age-related spinal degeneration [13,15].…”
Section: Discussionmentioning
confidence: 97%